Fractioning and chemical characterization of barks of Betula pendula and Eucalyptus globulus - Miranda, Isabel (2015)
The composition of birch (Betula pendula Roth.) and eucalypt (Eucalyptus globulus Labill.) barks was studied after grinding and fractioning into different particles sizes. There was a significant difference in the fractionation of both barks in relation to the yield of fines (5.9% and 28.3% of particles under 0.450 for birch and eucalypt, respectively) and of coarser particles over 2 mm (70.7% and 41.4%). The chemical composition of birch and eucalypt barks, as a mass weighed average of all granulometric fractions was, respectively: ash 2.9% and 12.1%; total extractives 17.6% and 6.5% (hydrophilic extractives were dominant), lignin 27.9% and 28.8% and holocellulose 49.8% and 62.6%. Birch bark contained a considerable amount of suberin (5.9%) whereas eucalypt bark contained a very small amount (<1%). The carbohydrate composition differed between birch and eucalypt barks, i.e., respectively, glucose 47.0% and 68.4%, and xylose 33.8% and 23.2% of total neutral monosaccharides. Ash elemental composition was different in both species. Birch bark contained in relation to eucalypt bark, in the 0.250–0.450 mm fraction, more N (0.69% vs. 0.26%) and P (0.075% vs. 0.001%), and less Ca (0.39% vs. 0.62%), K (0.24% vs. 0.31%) and Mg (0.07% vs. 0.15%). High concentration of Zn was found in birch bark (217 mg/kg vs. 11 mg/kg in eucalypt bark). After grinding and granulometric separation, extractives were present preferentially in the finest fraction with an enrichment in dichloromethane and ethanol solubles especially in the case of birch bark. Eucalypt bark had a high content of cellulose and hemicelluloses especially in the coarser fraction. The fibrous character of this fraction shows its potential as a fiber source